From global-to-local: rural mental health in South Africa - Richard Vergunst (Taylor & Francis Group, 2018)
In this paper, the current situation regarding rural mental health in South Africa is explored. The current status is presented, followed by an attempt to provide approaches and ideas to improve the situation in order to make it more context appropriate and relevant. Issues of staffing, task shifting or sharing, and formal vs informal health care systems are considered and discussed as possible future approaches to improve rural mental health care in South Africa.